Development e-module through problem-based learning on ecosystem concepts to improve environmental literacy - Silvi Puspa Widya Lubis; Handika Handika; Samsuar Samsuar (Universitas Negeri Jakarta, 2026)
This study developed an e-module based on problem-based learning (PBL) on ecosystem materials to enhance environmental literacy using the 3D model. The research novelty lies in the systematic integration of environmental literacy indicators directly into the PBL syntax, synchronizing ecosystem problem-solving with ecological knowledge. The development progressed through define, design, and development stages, involving rigorous competency analysis, interactive storyboarding, and expert validation. Results demonstrated an overall feasibility score of 74.8% (feasible), with the material expert rating it at 66.6% (Feasible) and the media expert at 83.3% (very Feasible). Based on these findings, it is recommended that educators utilize this e-module as a supplementary tool to foster environmental awareness. Furthermore, future development should refine the material depth by incorporating recent local ecological data and expanding into the Dissemination stage through large-scale field testing to measure long-term behavioral impacts. This digital-interactive approach effectively bridges abstract biological concepts with real-world environmental challenges for students.